2022
DOI: 10.1111/eci.13743
|View full text |Cite
|
Sign up to set email alerts
|

An observational study of the Covid‐19 situation following the first pan‐European mass sports event

Abstract: Background All events in Europe, including EURO2020 football championship, were postponed due to Covid‐19 in 2020. Instead, Euro2020 took place in 2021, as mitigation measures were relaxed, cross‐country mobility increased and the Delta variant was spreading across Europe. This study explored the possibility of an increased Covid‐19 spread across Europe following EURO2020 matches. Methods Covid‐19 data on cases, vaccination and delta variant for participating countries, host cities/regions and neighbouring cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…While stadium attendance might only have a minor effect [12][13][14], it increases TV viewer engagement [15][16][17] and encourages additional social gatherings [18]. These phenomena and previous observational analyses [19] suggest that the Euro 2020's impact may have been considerable. Therefore, we used this championship as a case study to quantify the impact of large events on the spread of COVID-19.…”
Section: Introductionmentioning
confidence: 64%
“…While stadium attendance might only have a minor effect [12][13][14], it increases TV viewer engagement [15][16][17] and encourages additional social gatherings [18]. These phenomena and previous observational analyses [19] suggest that the Euro 2020's impact may have been considerable. Therefore, we used this championship as a case study to quantify the impact of large events on the spread of COVID-19.…”
Section: Introductionmentioning
confidence: 64%
“…Four scholarly publications successfully were published targeting COVID-19 epidemiology across the Balkan countries [ 46 ], across microstates in Europe [ 47 ], across European countries [ 48 ], and the COVID-19 situation in Europe following the EURO2020 football tournament [ 49 ]. Another scholarly article was produced assessing the COVID-19 epidemiology across the Mediterranean region which has been accepted (but not yet published at the time of writing) in the journal African Health Sciences .…”
Section: Discussionmentioning
confidence: 99%
“…The study of Cuschieri et al [17], however, reported a contrast in the context of the EURO2020 football championship, which was the first pan-European mass sports event after the onset of the pandemic. Following the EURO2020 championships, a general increase in COVID-19 cases was observed both on the local (host cities/regions) and national (participating and non-participating countries) levels.…”
Section: Direct Effect On Transmissionmentioning
confidence: 98%